Gate dielectric material influence on DC behavior of MO(I)SHEMT devices operating up to 150 °C. (November 2021) - Agopian, P.G.D.; Carmo, G.J.; Martino, J.A.; Simoen, E.; Peralagu, U.; Parvais, B.; Waldron, N.; Collaert, N.
Abstract: In this work, the DC behavior of AlGaN/GaN Metal-Insulator-Semiconductor high electron mobility transistors (MO(I)SHEMTs) with two different gate dielectrics (Al2 O3 and Si3 N4 ) is analyzed through the experimental comparison of their basic and analog parameters. The transistors with Si3 N4 insulator are more closely related to the normally-off devices (less negative threshold voltage) and less affected by the short channel effects (better DIBL behavior). Although the devices with Si3 N4 layer presented a double conduction, that results in anomalous transconductance behavior, it is more suitable for analog applications since the Al2 O3 devices suffer large self-heating. The very high gate leakage of Si3 N4 MISHEMT degrades the subthreshold regime, which decreases the transistor efficiency at weak inversion. On the other hand, the devices with Si3 N4 insulator present relatively large Early voltage and consequently high intrinsic voltage gain in strong inversion, reaching 84 V/V (38.5 dB). Even at high temperatures the intrinsic voltage gain is practically the same, degrading only 1.5 dB from 25 °C to 150 °C for a long channel device.